Hapag-Kainan - De la Cruz, Christa I. (Likhaan: The Journal of Contemporary Philippine Literature; Vol 17 No 1 (2023): LIKHAAN 17: The Journal of Contemporary Philippine Literature, 2023)
"Hapag-Kainan,” a short story in Filipino, is set in the Philippines in 2050. it follows the story of Andrei, who’s also the narrator, and his friendship with Por. Por comes from the wealthy political family of the Marucuts, known for corrupt governance.